The cultural biography of agarwood: perfumery in Eastern Asia and the Asian neighbourhood - Jung, Dinah (Journal of the Royal Asiatic Society, 2013)
Agarwood (especially 〔 沉 香 〕 Chinese chen xiang / 〔 沈 香 〕 Japanese jinkō), among other subspecies differentiated in East Asian languages, has caught international perfumery attention in conspicuous dimensions in the past years. It belongs to the most sought after perfumery raw materials in the world. The lucrative image of its business makes international businessmen, foreign scientists, perfumers, global industry representatives, as well as locals eager to participate in its international distribution and to improve its artificial mass cultivation and synthetic production. Moreover, efforts transgress mere economic activities in Eastern Asia when perfumery devotees engage in historical research and perfumery experiments, or when they publish on their experiences, as well as when they establish networks with like-minded people.
Gesehen am 28.09.2017